Implementasi Supervisi Pendidikan dalam Meningkatkan Proses Pembelajaran - Maryati, Yati (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to describe the supervision activities carried out by the head of MTs Negeri 1 Prabumulih in improving the learning process carried out by teachers. In general, this study reveals that 1) The focus of supervision activities includes teacher administration and learning process activities; 2) Supervision activities are very helpful for teachers in solving educational problems faced by teachers during learning; 3) With supervision, teachers become more motivated to try to increase knowledge to become professional teachers in carrying out learning; 4) Obstacles faced by school principals in supervision are the number of activities, limited operational funds, and the COVID-19 pandemic which limits activities so that supervision which should be carried out twice becomes once a year.